VISUAL BRANDING HOT WATER BOOM SAPAN MALULUANG SOLOK SELATAN - VIVIEN DAMARA HANDINA, San Ahdi, S.Sn., M.Ds., Dr. M. Nasrul Kamal, M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
South Solok a blend lowland, and highlands interspersed with rivers and mountains with tropical forests are still beautiful, with such a natural condition that South Solok tourism store potentially very promising to be developed. One of the places from southern solok is Hot Water Boom Sapan Maluluang South Solok. The purpose of designing Visual Branding Hot Water Boom Sapan Maluluang South Solok hopes to bring a positive image through the approach of cultural values as well as introducing the assets owned by South Solok as a sustainable tourism destination.The concept of designing Visual Branding Hot Water Boom Sapan Maluluang Solok Selatan presents logogram and logotype taken from the concept that berakteristik in building verbal messages and visual messages. This design meteodology uses a SWOT analysis approach to find strengths, weaknesses, opportunities, and threats in developing the Hot Water Boom Sapan Maluluang Solok Selatan tour. Visual Branding Design Hot Water Boom Sapan Maluluang Solok Selatan applied to the main media manual book, and stationery set. Supporting media in the form of posters, x-Banners, mugs, stickers, t-shirts, brochures, and banners. Application of layout or layout of supporting media in accordance with the principles of design in order to get good results. The hope with the design of Visual Branding Hot Water Boom Sapan Maluluang South Solok can be a significant contribution through the creativity of creativity in supporting the tourism city of South Solok.Keywords: Visual Branding, Hot Water Boom, Sapan Maluluang Solok Selatan